1978
DOI: 10.1152/jn.1978.41.2.394
|View full text |Cite
|
Sign up to set email alerts
|

Vestibulothalamic projections in man--a sixth primary sensory pathway

Abstract: 1. Responses suggesting activation of the vestibular system, elicited by electrical stimulation of the human thalamus during 22 routine stereotaxic neurosurgical procedures, were examined in a retrospective study to determine the possible existence of vestibulothalamo-cortical projections in man. 2. Such responses were most frequently described as sensations of movement through space and were associated with two distinct vestibulothalamic projections: a) an anterior relay was situated ventral to the medial lem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
1

Year Published

1980
1980
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(29 citation statements)
references
References 0 publications
1
27
0
1
Order By: Relevance
“…Hawrylyshyn et al (1978) were able to evoke in conscious patients sensations of movement by stimulating a vestibulothalamic pathway "situated ventral to the medial lemniscus, passing lateral to the red nucleus and dorsal to the subthalamic nucleus prior to terminating in the Vim." A more recent study using H 2 15 O PET measurements demonstrated projections of the Vim to the parieto-insular vestibular cortex (PIVC), the main vestibular cortical area (Ceballos-Baumann et al, 2001).…”
Section: Neurological Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Hawrylyshyn et al (1978) were able to evoke in conscious patients sensations of movement by stimulating a vestibulothalamic pathway "situated ventral to the medial lemniscus, passing lateral to the red nucleus and dorsal to the subthalamic nucleus prior to terminating in the Vim." A more recent study using H 2 15 O PET measurements demonstrated projections of the Vim to the parieto-insular vestibular cortex (PIVC), the main vestibular cortical area (Ceballos-Baumann et al, 2001).…”
Section: Neurological Datamentioning
confidence: 99%
“…Therefore, by relaying vestibular cues, and particularly graviceptive cues, this thalamic region could be involved in encoding gravity and controlling body orientation in space. Finally, a contribution of the MGN has also been suggested in humans during neurosurgical explorations of the thalamus (Hawrylyshyn et al, 1978). Sensations of movements through space were evoked during the stimulation of a vestibulothalamic pathway "associated with the auditory pathway (lateral lemniscus and brachium of the inferior colliculus)" to the MGN.…”
Section: Neurological Datamentioning
confidence: 99%
“…Two ves tibular paths are represented, one traversing the lateral lemniscus and medial geniculate, the other the subthalamus and the target area in V.i.m. [3].…”
Section: Physiological Properties Of Lesion Areamentioning
confidence: 99%
“…Apparently intermingled with kinesthetic cells, we have found evi dence with macrostimulation, but not yet with microstimulation, for the rostral vestibulothalamic pathway described in subhuman primates, the stimulation of which induces a feeling of faintness, nausea or vertigo [17].…”
Section: The Rostral Vestibular Pathwaymentioning
confidence: 61%